Accuracy of joint line restoration based on three‐dimensional registration of the contralateral tibial tuberosity and the fibular tip - Sandro Hodel; Anna‐Katharina Calek; Philipp Fürnstahl; Sandro F. Fucentese; Lazaros Vlachopoulos (Journal of Experimental Orthopaedics, 2021)
Abstract Purpose To assess a novel method of three‐dimensional (3D) joint line (JL) restoration based on the contralateral tibia and fibula. Methods 3D triangular surface models were generated from computed tomographic data of 96 paired lower legs (48 cadavers) without signs of pathology. Three segments of the tibia and fibula, excluding the tibia plateau, were defined (tibia, fibula, tibial tuberosity (TT) and fibular tip). A surface registration algorithm was used to superimpose the mirrored contralateral model onto the original model. JL approximation and absolute mean errors for each segment registration were measured and its relationship to gender, height, weight and tibia and fibula length side‐to‐side differences analyzed. Fibular tip to JL distance was measured and analyzed. Results Mean JL approximation did not yield significant differences among the three segments. Mean absolute JL error was highest for the tibia 1.4 ± 1.4 mm (range: 0 to 6.0 mm) and decreased for the fibula 0.8 ± 1.0 mm (range: 0 to 3.7 mm) and for TT and fibular tip segment 0.7 ± 0.6 (range: 0 to 2.4 mm) (p = 0.03). Mean absolute JL error of the TT and fibular tip segment was independent of gender, height, weight and tibia and fibula length side‐to‐side differences. Mean fibular tip to JL distance was 11.9 ± 3.4 mm (range: 3.4 to 22.1 mm) with a mean absolute side‐to‐side difference of 1.6 ± 1.1 mm (range: 0 to 5.3 mm). Conclusion 3D registration of the contralateral tibia and fibula reliably approximated the original JL. The registration of, TT and fibular tip, as robust anatomical landmarks, improved the accuracy of JL restoration independent of tibia and fibula length side‐to‐side differences. Level of evidence IV